Bayesian meta-elliptical multivariate regression models with fixed marginals on unit intervals. Issue 3 (1st February 2023) - Rodrigues, Josemar; Benites, Yury R.; Cancho, Vicente G.; Balakrishnan, N.; Suzuki, Adriano K.
Abstract: In this paper, we make use of meta-elliptical copula functions to build a new multivariate distribution with fixed marginal distributions and dependence structure to analyze bounded data. Specifically, we present a flexible p-elliptical multivariate probability distribution in the hypercube ( 0, 1 ) p p with fixed marginal GF-quantile distributions. We then present some illustrative examples and a meta-elliptical multivariate regression model as a flexible alternative to the multivariate normal regression model on unit intervals. A simulation study and real-life data analysis using a Bayesian framework with the extreme-value quantile functions show the flexibility of the proposed meta-multivariate normal regression model for modeling the observed proportion response variables.